PHOTOALIGNMENT FILM, METHOD FOR MANUFACTURING THE SAME AND LIQUID CRYSTAL DISPLAY COMPRISING THE SAME - JUNG, JIN SOO; JEON, BAEK KYUN; LEE, HONG YEON; KANG, SUK HOON (2016)
The present invention provides a photoalignment film, a manufacturing method thereof, and a liquid crystal display panel including the same. Fibers made of a photoalignment material having optical anisotropy in one direction are stacked to form a fiber layer, with a major axis arranged in the one direction, and the fiber layer has a surface corrugated in accordance with a difference in a stacked height of the fibers. A side chain of a polymer is aligned in a certain direction, so the orientation of a liquid crystal is adjusted by chemical interaction between the side chain and a liquid crystal molecule. In addition, multiple grooves are formed regularly on a surface of the alignment film by rubbing, so the orientation of the liquid crystal is adjusted by mechanical interaction between the grooves and the liquid crystal. 본 발명은 일방향에 대해 광학 이방성을 가진 광배향 물질로 이루어진 섬유들이 장축이 상기 일방향으로 배열된 상태에서 적층되어 섬유층을 형성하고, 상기 섬유층은 상기 섬유들의 적층 높이 차이에 따른 굴곡진 표면을 가진 광배향막, 이의 제조방법 및 이를 포함하는 액정표시패널을 제공한다.